468. THE EFFECT OF ROUTINE ENDOSCOPIC SCREENING FOR SYNCHRONOUS ESOPHAGEAL NEOPLASIA IN PATIENTS WITH HEAD AND NECK SQUAMOUS CELL CARCINOMA. (24th September 2022) - Shimada, Ayako; Hirano, Yuki; Oyama, Takashi; Tamura, Takuya; Minagawa, Takuya; Ishida, Takashi; Tsuruta, Masashi; Hoshimoto, Sojun; Shinoda, Masahiro; Itano, Osamu
Abstract: Esophageal squamous cell carcinoma (ESCC) and head and neck (H&N) cancer coincide in high frequency and early detection of synchronous cancer is inevitable for these patients. The aim of this study is to analyze the effect of routine endoscopic screening for synchronous esophageal cancer in patients with H&N cancer. From April 2020 to March 2022, 35 patients with newly-diagnosed H&N cancer had routine screening endoscopy for synchronous esophageal cancer. All patients with H&N cancer were referred to our department prior to the treatment for H&N cancer. The locations of H&N cancers were oral/oropharyngeal/hypopharyngeal/laryngeal/other H&N cancer; 9/6/9/9/2 respectively. Image-enhanced endoscopy using BLI (blue laser imaging) was performed in all patients. Lugol staining was used in 20 patients and multiple Lugol voiding lesions were detected in 9 patients. Among all patients, abnormal endoscopic findings in esophagus were detected in 15 patients (43%), and biopsy was performed in 11 patients (31%). Biopsy revealed SCC in 5 patients and atypical epithelium in 2 patients. Esophageal lesions were all found in early stage within indication of endoscopic treatment. 3 patients underwent endoscopic treatment after treatment of H&N cancer. Routine endoscopic screening for patients with H&N cancer is effective in early detection of synchronous esophageal cancer with minimally invasive treatment for esophageal neoplasm. The treatment of chemotherapy for H&N cancer may be effective for esophageal lesions, therefore, careful surveillance is required during the treatment of H&N cancer. Routine endoscopy should be continued further for these patients for screening of metachronous cancer.